2016
DOI: 10.2334/josnusd.58.93
|View full text |Cite
|
Sign up to set email alerts
|

Use of a laser displacement sensor with a non-contact electromagnetic vibration device for assessment of simulated periodontal tissue conditions

Abstract: A non-contact electromagnetic vibration device (NEVD) was previously developed to monitor the condition of periodontal tissues by assessing mechanical parameters. This system requires placement of an accelerometer on the target tooth, to detect vibration. Using experimental tooth models, we evaluated the performance of an NEVD system with a laser displacement sensor (LDS), which does not need an accelerometer. Simulated teeth (polyacetal rods) were submerged at various depths in simulated bone (polyurethane or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The increased mechanical parameter values observed in Group C may be caused by the decrease in mass of the simulated tooth. A recent study [ 16 ] has shown that more accurate mechanical parameters were obtained when using LDS with NEVD compared to using accelerometer with NEVD in the experimental bone destruction models. This report suggested that the actual total mass of the simulated tooth due to the absence of accelerometer could contribute to more accurate mechanical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased mechanical parameter values observed in Group C may be caused by the decrease in mass of the simulated tooth. A recent study [ 16 ] has shown that more accurate mechanical parameters were obtained when using LDS with NEVD compared to using accelerometer with NEVD in the experimental bone destruction models. This report suggested that the actual total mass of the simulated tooth due to the absence of accelerometer could contribute to more accurate mechanical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…One of the noncontact types is a laser displacement sensor (LDS), which can measure the distance as well as the acceleration of the target object without mechanical contact (cordless) [ 13 15 ]. A recent study [ 16 ] revealed that the application of the LDS, instead of the accelerometer, to NEVD can detect the different degrees of simulated bone destruction and qualities using the in vitro experimental tooth models.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not use either material in our study due to their difficult processability; instead, melamine resin was used owing to its ease of handling. Previous studies have also reported the use of simulated periodontal ligaments made using soft lining materials 27,28 or silicone impression materials 22,23,25,26 . However, the former were consid ered inappropriate here as they harden over a period of time; hence, a silicone rubber material was used for the dental impressions owing to its excellent dimensional stability.…”
Section: Methods Used In This Studymentioning
confidence: 99%
“…Using laser displacement sensor with this device could also provide better clinical operability by eliminating the attachment of an accelerometer that is connect to the fast Fourier transformation analyser by the cord. [33] These methods are either tedious, complex and/or exorbitant for routine clinical application. The investigator requires training for the reproducibility of the results.…”
Section: Nevd-non-contact Electromagnetic Vibration Device (2016)mentioning
confidence: 99%